2000
DOI: 10.1046/j.1462-5822.2000.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathogenic Escherichia coli (EPEC) attachment to epithelial cells: exploiting the host cell cytoskeleton from the outside

Abstract: SummaryEnteropathogenic Escherichia coli (EPEC), a leading cause of human infantile diarrhoea, is the prototype for a family of intestinal bacterial pathogens that induce attaching and effacing (A/E) lesions on host cells. A/E lesions are characterized by localized effacement of the brush border of enterocytes, intimate bacterial attachment and pedestal formation beneath the adherent bacteria. As a result of some recent breakthrough discoveries, EPEC has now emerged as a fascinating paradigm for the study of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 58 publications
1
66
0
3
Order By: Relevance
“…This important virulence determinant is required for the formation of the characteristic Quorum sensing in bacterial virulence -a review attaching and effacing (AE) lesions caused by these pathogens (Celli et al, 2000). Additionally, transcriptomic studies have revealed that LuxS is a global regulator in EHEC, controlling the expression of over 400 genes (DeLisa et al, 2001;Sperandio et al, 2001).…”
Section: Quorum Sensing In Escherichia Coli Virulencementioning
confidence: 99%
“…This important virulence determinant is required for the formation of the characteristic Quorum sensing in bacterial virulence -a review attaching and effacing (AE) lesions caused by these pathogens (Celli et al, 2000). Additionally, transcriptomic studies have revealed that LuxS is a global regulator in EHEC, controlling the expression of over 400 genes (DeLisa et al, 2001;Sperandio et al, 2001).…”
Section: Quorum Sensing In Escherichia Coli Virulencementioning
confidence: 99%
“…This lesion is the direct consequence of an adhesin known as intimin that allows the E. coli to adhere to the intestinal epithelium of its host cells [6]. Its adherence to the intestinal mucosa causes a rearrangement of the actin in the host cell, resulting in significant deformation [7]. However, the exact mechanisms of diarrhea in EPEC infection are not completely understood [8,2].…”
Section: Introductionmentioning
confidence: 99%
“…Enteropathogenic E. coli (EPEC) is a food-borne pathogen and a major cause of watery infantile diarrhea worldwide that is associated with high rates of morbidity and mortality. A unique feature of EPEC is that it neither expresses toxins nor is invasive but instead attaches intimately to host intestinal epithelial cells (3,4). The pathogenicity island of EPEC houses a number of virulence proteins including those of a type III secretion system (TTSS) through which bacteria directly deliver their proteins into the host cell (5,6).…”
Section: Introductionmentioning
confidence: 99%